2008
DOI: 10.1097/tp.0b013e3181735723
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Survival in Intragraft Tertiary Lymphoid Organs After Rituximab Therapy

Abstract: In certain patients, inflammatory microenvironment provides BAFF-dependent paracrine survival signal to B-cells in TLOs, allowing them to escape rituximab-induced apoptosis, thereby thwarting therapeutic efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 17 publications
10
94
2
Order By: Relevance
“…Our group (18,21,23) and others (17,41) have contributed to document the role of lymphoid neogenesis, namely, the progressive organization of inflammatory cells into structures that morphologically resemble secondary lymphoid organs (42) during chronic rejection. Accumulating evidence indeed suggests that intragraft ectopic germinal centers support the maturation of a local humoral immune response, which in turn contributes to tissue destruction (21)(22)(23). The close correlation observed between the levels of expression of AID (the key enzyme in the germinal center reaction) and IL-21 leads us to propose that Th17 cells hasten graft destruction by promoting lymphoid neogenesis through the production of IL-21.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our group (18,21,23) and others (17,41) have contributed to document the role of lymphoid neogenesis, namely, the progressive organization of inflammatory cells into structures that morphologically resemble secondary lymphoid organs (42) during chronic rejection. Accumulating evidence indeed suggests that intragraft ectopic germinal centers support the maturation of a local humoral immune response, which in turn contributes to tissue destruction (21)(22)(23). The close correlation observed between the levels of expression of AID (the key enzyme in the germinal center reaction) and IL-21 leads us to propose that Th17 cells hasten graft destruction by promoting lymphoid neogenesis through the production of IL-21.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have indeed reported that intragraft ectopic germinal centers are the site of elicitation of a local humoral immune response (18,(21)(22)(23).…”
Section: Intragraft Il21 Promotes Lymphoid Neogenesismentioning
confidence: 99%
“…Tertiary lymphoid structures have been detected in peripheral lymphoid organs in a variety of autoimmune diseases and in graft rejection (Thaunat et al, 2008). In this situation, their increase in size and number correlates with disease severity and local production of autoantibodies with an oligoclonal repertoire and hypersomatic mutations (Gause et al, 1995;Kotlan et al, 2003;RangelMoreno et al, 2006;Carragher et al, 2008;Humby et al, 2009).…”
Section: Immune Infiltration In Human Tumorsmentioning
confidence: 99%
“…The existence of this lymphoid neogenesis in the aorta might impair the efficiency of therapeutic strategies targeting the immune system, such as B2 cell depletion, as it occurs in other chronic inflammatory settings such as chronic graft rejection. For instance, rituximab (anti-CD20 antibody) treatment, which depletes circulating B cells, failed to eliminate the intragraft B cells in the context of renal allograft (where TLOs develop in the interstitium of the graft) and local alloantibody production persisted (34). This might be due to the enrichment in B-cell survival factors within the graft inflammatory microenvironment.…”
Section: Where Is This Adaptive Immune Response Generated: Faraway Lymentioning
confidence: 95%
“…Interestingly, in line with the proatherogenic role of B2 cells, it has been suggested that rituximab (anti-CD20) can become a treatment in atherosclerosis (19,20). However, it would be important to verify that this treatment also depletes B cells from TLOs during atherosclerosis, considering that this is not the case in the context of allograft (34), and that aortic TLOs are sites of B-cell activation (29). Another strategy to impair B2 cell function would be to block their activation by Tfh cells.…”
Section: Apoementioning
confidence: 99%